Optimasi Adsorpsi Ion Mg2+ pada Fixed Bed Column dengan Menggunakan Response Surface Methodology - Novi Sylvia; Meriatna Meriatna; Fikri Hasfita; Lukman Hakim (Reaktor, 2017)
Abstract OPTIMIZATION ADSORPTION OF Mg2+ ION ON FIXED BED COLUMN USING RESPONSE SURFACE METHODOLOGY. Modeling of the adsorption process is used to establish the mathematical relationship between the interacting process variables and process optimization. This is important to determine the factor values that produce a maximum response. Adsorption of Mg from groundwater was optimized using response surface methodology based on Box-Behnken design was used to analyze adsorption data. The process was investigated by continuous experiments. Variables included in the process were: bed depths (7.5, 10, and 12.5 cm), time (20, 40, and 60 min), and flow rate (6, 10, and 14 L/min). Regression analysis was used to analyze the developed models. The outcome of this research showed that 72.784% of the variability in removal efficiency is attributed to the three process variables considered, that is, bed depths, time, and flow rate. Optimization tests showed that the optimum operating conditions for the adsorption process occurred at a bed depth of 11.37 cm, time of 55.53 min and flow rate of 6 L/min. Keywords: adsorption; Box-Behnken design; magnesium (Mg2+); optimization  AbstrakPemodelan dari proses adsorpsi digunakan untuk menentukan hubungan matematis antara variabel proses interaksi dan proses optimasi. Hal ini penting untuk menentukan nilai faktor yang menghasilkan respon maksimum. Adsorpsi magnesium (Mg2+) dari air tanah dioptimalkan menggunakan metodologi respon permukaan model Desain Box-Behnken yang digunakan untuk menganalisis data adsorpsi. Percobaan dilakukan secara kontinyu. Variabel yang termasuk dalam proses tersebut adalah: tinggi unggun (7,5, 10 dan 12,5 cm), waktu kontak (20, 40, dan 60 menit), dan laju alir (6, 10, dan 14 L/menit). Analisis regresi digunakan untuk menganalisis model yang dikembangkan. Hasil penelitian menunjukkan bahwa 72,784% efisiensi penyisihan Mg2+ ditentukan oleh tiga variabel proses, yaitu tinggi unggun, waktu kontak, dan laju alir. Hasil optimasi menunjukkan bahwa kondisi operasi optimum untuk proses adsorpsi terjadi pada tinggi unggun 11,37 cm, waktu kontak 55,53 menit dan laju alir 6 L/menit. Kata kunci: adsorpsi; Box-Behnken desain; magnesium (Mg2+); optimasi